Aktivitas Antibakteri Ekstrak Bunga Telang (Clitoria ternatea L) terhadap Pertumbuhan Bakteri Staphylococcus aureus dan Escherichia coli - Widyasanti, Asri; Febrianti, Febrianti (Universitas Trunojoyo Madura, 2024)
Clitoria ternatea L. or commonly called butterfly pea is a vine that belongs to the fabaceae family. This plant is known to provide many benefits, one of which is as a natural antibacterial. Secondary metabolite compounds in C. ternatea are thought to be responsible for its antimicrobial activity. The purpose of this study was to determine the antibacterial activity of C. ternatea extract in inhibiting the growth of S. aureus and E. coli bacteria and to determine the interaction between the concentration of the extract and its growth. The method used was an experiment with a completely randomized design (CRD). The treatments given were variations in the concentration of C. ternatea extract by 20%, 40%, 60%, 80%, and 100%, positive control of meropenem and negative control of aquades. The C. ternatea extracts were also screened for phytochemicals for flavonoids, saponins, tannins, alkaloids, and phenols which showed positive results for these five compounds. The results of antibacterial testing proved that C. ternatea extract could inhibit the growth of S. aureus and E. coli bacteria and the concentration treatment had a very significant effect on the zone of inhibition. The antibacterial activity of C. ternatea extract was most effective at a concentration of 100% with the mean value of DDH against S. aureus bacteria was 8.44 ± 0.27 mm while against E. coli bacteria was 10.00 ± 0.73 mm. The concentration treatment of the tested C. ternatea extract had a very significant effect on the zone of inhibition of the two bacteria.